Risk Management Concept Development of Pondok Pesantren Educational Institutions - Ekaningsih, Lely Ana Ferawati; Salim, Ubud; Djumahir, Djumahir; Indrawati, Nur Khusniyah; Djakfar, Muhammad (Future Science / FSH-PH Publications, 2022)
The concept of risk management has been widely studied in terms of finance in Islamic and conventional banking, government institutions, and insurance. While research on non-financial risk management in educational institutionsis still rarely done. This article aims to propose the development of the concept of risk management for Islamic educational institutions, especially pondokpesantrenor Islamic boarding schools. This research is a qualitative research/conceptual paper by conducting theoretical and empirical studies on articles that have been published. The data is secondary data. The results of the study found that risk exists in all organizations including pondokpesantren, so it is necessary to carry out risk management. Risk must be managed appropriately and correctly because failure to manage risk has serious consequences for the organization. The risk management process in pondokpesantrenis based on the implementation of Islamic values ​​sourced from the Qur'an and Hadith. The most important contribution of this paper is to develop the concept of risk management for pondokpesantren.